Financing Long‐Term Care: Ex Ante, Ex Post or Both?. (March 2015) - COSTA‐FONT, Joan; Courbage, Christophe; Swartz, Katherine
Abstract: This paper attempts to examine the heterogeneity in the public financing of long‐term care (LTC) and the wide‐ranging instruments in place to finance LTC services. We distinguish and classify the institutional responses to the need for LTC financing as ex ante (occurring prior to when the need arises, such as insurance) and ex post (occurring after the need arises, such as public sector and family financing). Then, we examine country‐specific data to ascertain whether the two types of financing are complements or substitutes. Finally, we examine exploratory cross‐national data on public expenditure determinants, specifically economic, demographic and social determinants. We show that although both ex ante and ex post mechanisms exist in all countries with advanced industrial economies and despite the fact that instruments are different across countries, ex ante and ex post instruments are largely substitutes for each other. Expenditure estimates to date indicate that the public financing of LTC is highly sensitive to a country's income, ageing of the population and the availability of informal caregiving. Copyright © 2015 John Wiley & Sons, Ltd.